RELATIONSHIP BETWEEN RED BLOOD CELL AND PLATELET INDICES IN IRON DEFICIENCY ANEMIA - Sahar Rabbani (Army Medical College Rawalpindi, 2021)
Objective: To find out the correlation between the red blood cell and platelet indices in patients presenting with iron deficiency anemia at a tertiary care hospital of Pakistan.